Decision Modeling for Appraising Material Handling Equipments under Qualitative Indices - Sahu, Atul Kumar; Narang, Harendra Kumar; Rajput, Mridul Singh (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*306.65px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920591);" role="presentation">Material handling equipments (MHEs) are the important part of every manufacturing and <span dir="ltr" style="left: calc(var(--scale-factor)*432.46px); top: calc(var(--scale-factor)*306.65px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953737);" role="presentation">industrial firms, which <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*319.85px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943185);" role="presentation">remains involved during the process of manufacturing, distribution, consumption, disposal etc. Assessing the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*333.05px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9887);" role="presentation">importance of MHE is crucial and it can influence the profit of the concerned firm. Thus, in this work, the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909957);" role="presentation">authors respond<span dir="ltr" style="left: calc(var(--scale-factor)*137.66px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963113);" role="presentation">ed towards MHE characteristics and equipped an assessment platform for appraising MHE <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*359.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940055);" role="presentation">indices, which can be utilized in defining the status of the indices relating the MHE. A Multi-<span dir="ltr" style="left: calc(var(--scale-factor)*449.02px); top: calc(var(--scale-factor)*359.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944933);" role="presentation">Criterion Decision <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*372.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.987024);" role="presentation">Making (MCDM) framework under the arena of Material Hand<span dir="ltr" style="left: calc(var(--scale-factor)*339.67px); top: calc(var(--scale-factor)*372.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.985667);" role="presentation">ling Equipment (MHE) is developed by the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*385.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902069);" role="presentation">authors and a decision support model is presented by the authors to describe the level of the indices pertaining to <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*399.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922452);" role="presentation">the selection of MHE. Modeling based on Generalized Interval-<span dir="ltr" style="left: calc(var(--scale-factor)*328.03px); top: calc(var(--scale-factor)*399.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938605);" role="presentation">Valued Trapezoidal Fuzzy Numbers (GIVT<span dir="ltr" style="left: calc(var(--scale-factor)*503.52px); top: calc(var(--scale-factor)*399.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921658);" role="presentation">FNs) <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*412.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9807);" role="presentation">is presented to reciprocate towards the uncertainty and impreciseness of the MHE indices. A single level <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*425.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925405);" role="presentation">hierarchy platform is presented by the authors for demonstrating the scientific realization of the projected work. <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*438.91px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963777);" role="presentation">A fuzzy performance important i<span dir="ltr" style="left: calc(var(--scale-factor)*207.77px); top: calc(var(--scale-factor)*438.91px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954891);" role="presentation">ndex framework for MHE indices is discussed in this study to recognize the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*452.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92523);" role="presentation">strong and ill MHE indices. In this study, the authors presented a decision support framework, which can clutch <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*465.31px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972206);" role="presentation">the subjective views of the decision makers. In this study, the chief <span dir="ltr" style="left: calc(var(--scale-factor)*360.31px); top: calc(var(--scale-factor)*465.31px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972416);" role="presentation">objective of the authors is to distribute <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*478.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926049);" role="presentation">methodological way for determining the importance of distinguishes MHE indices.